ФОРМУВАННЯ ВИКОНАВСЬКИХ УМІНЬ У КЛАСІ ОСНОВНОГО ІНСТРУМЕНТА (ФОРТЕПІАНО) (Педагогіка вищої та середньої школи, 2006)
In clause conditions of development of pianistic performing skills of the future teachers of music are considered. The typology of performing skills and ways of their formation is offered.